Some Integral Inequalities of Hermite-Hadamard Type for Convex Functions with Applications to Means - Bo-Yan Xi; Feng Qi (Journal of Function Spaces and Applications)
The authors establish some new inequalities for differentiable convex functions, which are similar to the celebrated Hermite-Hadamard's integral inequality for convex functions, and apply these inequalities to construct inequalities for special means of two positive numbers.